2008
DOI: 10.1111/j.1365-3148.2008.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella henselaesurvives after the storage period of red blood cell units: is it transmissible by transfusion?

Abstract: Bartonella henselae is the agent of cat scratch disease and bacillary angiomatosis. Blood donors can be asymptomatic carriers of B. henselae and the risk for transmission by transfusion should be considered. The objective of this study was to demonstrate that B. henselae remains viable in red blood cell (RBC) units at the end of the storage period. Two RBC units were split into two portions. One portion was inoculated with B. henselae and the other was used as a control. All units were stored at 4 degrees C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
0
23
0
2
Order By: Relevance
“…berkhoffii and B. henselae transmission to children in utero or during caesarean section has been reported (Breitschwerdt et al 2010b). In addition, the ability of B. henselae to adhere and invade mature human erythrocytes (Pitassi et al 2007) and remain viable in red blood cells after 35 days of storage at 4ºC (Magalhães et al 2008) underscore the possibility that these organisms may be transmitted by blood transfusion (Magalhães et al 2009, Velho 2009). Although immunocompromised patients may present with a systemic and fatal disease, immunocompetent individuals infected with Bartonella spp may develop non-specific and usually non-life-threatening clinical symptoms that have a significant impact on quality of life (Breitschwerdt et al 2008, 2010a, b, Kaiser et al 2011, Kalogeropoulos et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…berkhoffii and B. henselae transmission to children in utero or during caesarean section has been reported (Breitschwerdt et al 2010b). In addition, the ability of B. henselae to adhere and invade mature human erythrocytes (Pitassi et al 2007) and remain viable in red blood cells after 35 days of storage at 4ºC (Magalhães et al 2008) underscore the possibility that these organisms may be transmitted by blood transfusion (Magalhães et al 2009, Velho 2009). Although immunocompromised patients may present with a systemic and fatal disease, immunocompetent individuals infected with Bartonella spp may develop non-specific and usually non-life-threatening clinical symptoms that have a significant impact on quality of life (Breitschwerdt et al 2008, 2010a, b, Kaiser et al 2011, Kalogeropoulos et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Contact with animals and vectors seem to be the most important mode of transmission, although recent studies have shown the ability of Bartonella to survive in stored blood for more than 35 days with the potential for transfusion-associated infection (Magalhães et al 2007).…”
mentioning
confidence: 99%
“…Besides, it was impossible to detect, in an free fleas environment, venereal transmission among bacteremic animals and among the queen and her kittens during the pregnancy and neonatal period (Abbot et al, 1997;Guptill et al, 1997;Guptill et al, 1998). However, another study showed the possibility of transmiting the agent B. henselae by blood transfusions (Magalhães et al, 2008).…”
Section: Transmission Among Catsmentioning
confidence: 99%